Holism and Individualism in Aldo Leopold’s Land Ethic - Kalenda, Česlovas (Problemos, 2001)
The article analyses the ecological ethic system of American ecologist Aldo Leopold (1886-1948). The author himself named it land ethic. It represents one of the first developed conceptions of modern ecological ethic. The evolutionary and the ecological biology and the evolutionary ethic are its sources. The ecological purpose of Leopold's ethic determined the holistic character of this ethic at doctrine. However the holism of land ethic does not deny individualism: in relation to the whole, the individual remains relatively independent.
Keywords: ecological ethics; evolutionary ethics; holism